The Role of Product Innovation Mediation in the Relationship between Market Orientation and Competitive Advantage in Culinary Sector MSMEs - Feliks Anggia Binsar Kristian Panjaitan; Muhammad Taali (Westscience Press, 2026)
This study aims to examine the mediating role of product innovation in the relationship between market orientation and competitive advantage among Indonesian culinary sector Micro, Small, and Medium Enterprises (MSMEs). A quantitative research design was employed using survey data collected from 200 MSME owners and managers. The measurement instrument utilized a five-point Likert scale, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that market orientation has a significant positive effect on product innovation and competitive advantage. Product innovation also shows a strong and significant influence on competitive advantage, highlighting its role as a key strategic capability in the culinary industry. Furthermore, mediation analysis confirms that product innovation partially mediates the relationship between market orientation and competitive advantage, suggesting that the ability to transform market insights into innovative products strengthens business competitiveness. The findings emphasize the importance of integrating customer focus, competitor awareness, and innovation strategies to achieve sustainable competitive advantage. This study contributes to the literature on strategic entrepreneurship and MSME competitiveness by providing empirical evidence from the Indonesian culinary sector and offers practical implications for business owners and policymakers in promoting innovation-driven development.